Charge Transport in Pure and Mixed Phases in Organic Solar Cells. Issue 20 (10th July 2017) - Melianas, Armantas; Pranculis, Vytenis; Spoltore, Donato; Benduhn, Johannes; Inganäs, Olle; Gulbinas, Vidmantas; Vandewal, Koen; Kemerink, Martijn
Abstract: In organic solar cells continuous donor and acceptor networks are considered necessary for charge extraction, whereas discontinuous neat phases and molecularly mixed donor–acceptor phases are generally regarded as detrimental. However, the impact of different levels of domain continuity, purity, and donor–acceptor mixing on charge transport remains only semiquantitatively described. Here, cosublimed donor–acceptor mixtures, where the distance between the donor sites is varied in a controlled manner from homogeneously diluted donor sites to a continuous donor network are studied. Using transient measurements, spanning from sub‐picoseconds to microseconds photogenerated charge motion is measured in complete photovoltaic devices, to show that even highly diluted donor sites (5.7%–10% molar) in a buckminsterfullerene matrix enable hole transport. Hopping between isolated donor sites can occur by long‐range hole tunneling through several buckminsterfullerene molecules, over distances of up to ≈4 nm. Hence, these results question the relevance of "pristine" phases and whether a continuous interpenetrating donor–acceptor network is the ideal morphology for charge transport. Abstract : Transient measurements reveal that in organic solar cells a continuous donor network is not strictly necessary for hole transport . Hole hopping between isolated donor sites can occur by long‐range hole tunneling through several buckminsterfullerene molecules (4 nm). This often disregarded mechanism questions the importance of pristine phases and whether a continuous donor–acceptor network is the ideal morphology for charge transport.